"Ecological risk assessments and eco-toxicity analyses using chemical, biological, physiological responses, DNA damages and gene-level biomarkers in Zebrafish (Danio rerio) in an urban stream". (January 2020) - Moon, Won-Ki; Atique, Usman; An, Kwang-Guk
Abstract: We conducted the ecological risk assessment in an urban stream by using multiple-level approaches ranging from community level, chemical analyses in water and sediments, physiological assays of DNA biomarkers, embryonic development tests, and gene-level marker analyses of cyp1a, c- Fos, CRH, transgenic fli1 :GFP and HuC:eGFP in zebrafish ( Danio rerio ). In water, the chemical perturbations based on nutrients (N, P), organic matter, ionic contents and metals identified in downstream zone. Analogous corroborations verified in sediment samples having hazardous metals (Zn, Pb, Cu, Ni, As, Cd). The chemical contaminations reflected significant damages in fish DNA, based on tDNA, tail length (TL), and tail extent moment (TEM). Zebrafish embryonic development experiments significantly enlightened the chemical contaminants in downstream compared to those in control and reference conditions. Hatching and survival rates rigorously declined in downstream region. Embryonic development delayed and followed by death in the downstream substantiated by the above-mentioned findings. Similar were the findings on heart rate and pigmentation largely affected in the contaminated zone. Pollutants in urban stream reflected significantly at the gene level, and were corroborated through experiments using transgenic zebrafish strains that were influenced by pollutants during the process of occurrence. In conclusion, these studies illuminate the community to gene-level ecological health assessment that could be useful for ecological risk assessments of urban streams and rivers. Further, the gene-level biomarkers and transgenic zebrafish experiments combination propose the procedures could be effectively used as sensitive and efficient biomarkers of ecological health and risk assessment in urban streams from community to gene-level assessments. Graphical abstract: Image 1 Highlights: Pollutant toxicity to zebrafish embryos was significantly higher in impacted zone as compared to control and reference zones. Aquatic pollutants affect hatching rate, embryo survival, heart rate in zebrafish. Melanogenesis, cypi1a, c- Fos, CRH and neurons generation were significantly higher in impacted sites. Outcomes of ecological health, metals in water and sediments and biomarkers corroborated with each other.